Electrical transport properties of peptide nanotubes coated with gold nanoparticles via peptide-induced biomineralization - Shekhar, Shashank (Nanotechnology, 2011)
We present temperature dependent electrical transport measurements of peptide nanotube devices coated with monodisperse arrays of gold nanoparticles (AuNP). As the temperature is lowered, the current–voltage (I–V ) characteristics become increasingly nonlinear and below 20 K conduction only occurs above a threshold voltage V(T). The current follows the scaling behavior I ∝ [(V − V(T))/V(T)](α) for V > V(T) with α ~ 2.5 signifying two-dimensional (2D) charge transport. The temperature dependence of the resistance shows thermally activated behavior with an activation energy of 18.2 meV corresponding to the sequential tunneling of charges through 6 nm monodispersed AuNP arrays grown on a peptide surface.